HPV vaccination in boys and men - Stanley, Margaret (Landes Bioscience, 2014)
Human papillomaviruses are DNA viruses that infect skin or mucosal cells. In the genital tract HPV (especially types 6 and 11) cause genital warts, the commonest viral sexually transmitted disease. At least 13 of the more than 100 known HPV genotypes are oncogenic “high-risk” genotypes. The 2 most common of these (genotypes 16 and 18) cause approximately 70% of all cervical cancers. Oncogenic HPVs particularly HPV 16 are associated with other anogenital cancers, anus, vagina, vulva and penis, and cancers of the head and neck and current estimates are that 5.2% of all cancers are HPV associated. In industrialised countries cervical cancer is controlled by secondary intervention other HPV associated malignancies are increasing in incidence and the burden of HPV associated disease in men is now comparable to that in women in economically developed countries. Randomized control trials with the quadrivalent HPV VLP vaccine demonstrate robust antibody responses and high efficacy against genital warts anal precancers in men. Few countries have recommended male vaccination on the basis that this is not cost effective. However gender-neutral vaccination has been recommended in the USA, Canada, Austria, and Australia. Careful cost effective modeling has preceded these decisions showing that when the burden of disease in men is included in the models then, depending upon coverage, vaccine price, and other factors male vaccination can become cost effective.